A systematic approach to the optimal design of chemical plants with waste reduction and market uncertainty. (12th July 2017) - Sepiacci, Piernico; Depetri, Valentina; Manca, Davide
Graphical abstract: Highlights: Assessment of economic and environmental sustainability by an innovative method. Rigorous approach to industrial sustainability under markets uncertainty. Dynamic econometric models of commodities and utilities for OPEX terms. Environmental impact of chemical plants with WAR algorithm. Multi objective optimization of a cumene plant along the Pareto line. Abstract: The paper presents a methodology for the quantitative assessment of sustainability applied to the design of chemical plants. Specifically, we focus on the economic and environmental sustainability. The methodology implemented for the economic assessment is the predictive conceptual design (PCD) that uses as indicator the cumulated dynamic economic potential over a long-term horizon. PCD accounts for both CAPEX and OPEX terms, which on their turn depend on dynamic econometric models of commodities and utilities. The environmental assessment is based on the waste reduction algorithm and on the evaluation of the potential environmental impact. The benefit of PCD consists in accounting for market uncertainty and prices/costs volatility of OPEX terms. The optimal solutions of the economic and environmental assessment lay on the Pareto line produced by the multi-objective-optimization (MOO) problem. The MOO of a cumene plant allows discussing various optimal solutions in terms of economic and environmental concerns/criteria.